ANALISIS DESAIN FORMULIR RESUME MEDIS DI RSUD KOTA SALATIGA - Lina Umboro Setyowati (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Medical records aimed at the orderly administration in an effort to improve health services in the hospital. One of the forms used in the inpatient medical record service is a medical resume . The medical resume form in hospitals Salatiga still did not agree with the theory, from the aspect of anatomy, physical and contents. This study aimed to analyze the design of medical resume form in Salatiga City Hospital from the aspect of anatomy, physical and contents. And also provide design solutions design medical resume form accordingly. This type of research is descriptive qualitative research. This research was conducted in Salatiga City Hospital on May 19 to May 26 in 2016, using the method of observation, interviews, documentary studies and FGD (Focus Group Discussion). Data processing techniques used in this study is reduction, display, conclusion drawing and verification. Observations based design medical resume form in Salatiga City Hospital that aspect has not been included heading anatomy complete form and lack of instruction. From the physical aspect is not well seen from the still opaque paper with a weight of 60 grams. While aspects of the content has been effective because it has provided to record the necessary data to the back of the form, but there has been no cause of death certificates.